THE IMPACT OF STIGMATIZATION ON PEOPLE WHO EXPOSED TO COVID-19 IN INDONESIA - Sakroni; Windriyati (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
An emerging social phenomenon has arisen in the midst of the COVID-19 epidemic that has the potential to worsen the situation: social stigma or unfavorable connections with a person or group of individuals who exhibit symptoms or have specific diseases.They are stigmatized, stereotyped, discriminated against, treated differently, and/or subjected to status harassment as a result of being associated with a medical condition. Stigma will in fact cause the spread of disease in society to become increasingly out of control. In the study of Medical and Biological Sciences, it is clear that the SARS-CoV2 virus as the cause of Covid-19 is a virus that only has RNA genetic material. This virus can only be active (live) in other cells as its host and as long as the cell is active. It can only be transmitted if a person sneezes, coughs, speaks with a droplet or saliva that carries the virus in it. This is the mode of transmission, so keeping your distance and always wearing a mask will reduce your risk of exposure. Maintaining distance does not mean cutting off contact with other people socially, so WHO also changes the phrase social distancing to physical distancing. The aim is that the global community will no longer cut off social contact with family or other people, but only maintain physical distance. Education is one of the most effective methods of reducing social stigma. In order to contribute to the normalization of the illness, regional or central officials who test positive for Covid-19 must be forthright about their diagnosis. Many forms of education can be carried out, such as socialization through social media and giving the public leaflets about how to transmit.